Teacher readiness for Maths and Science in English: A study of five secondary schools in Shah Alam / Fauziah Abdul Rahman - Abdul Rahman, Fauziah (2005)
The medium of instruction in schools has been an item that has been frequently discussed as the Malaysian Government changed the medium of instruction of two important subjects, Mathematics and Science to English in January 2003. This study looks at teacher readiness to teach Mathematics and Science in English. Are the teachers ready to use English in their teachings? Are they facing any difficulties or problems in doing so? Based on quantitative and qualitative methods, a survey was carried out in five secondary schools in Shah Alam, Selangor. The Sample consists of teachers teaching Mathematics and Science in forms one and two in the selected five secondary schools. The findings show that the teachers are ready to teach the two subjects in English, However, there are some areas that they are having difficulties with and it is found that the difficulties or problems faced by these teachers are similar in the schools surveyed. Some recommendations are made based on the findings in the survey and in the interviews in the hope that it would further improve the teaching of Mathematics and Science in English in our schools in Malaysia.